INFLUENCE OF CLIMATE INDICES ON VEGETATION DYNAMICS IN KAMUKU NATIONAL PARK, NIGERIA USING COUPLED MODEL INTERCOMPARISON PROJECT PHASE 6 (CMIP6) - Mustapha Baba, Bashariya; isa, zaharaddeen; Faruq Abdussalam, Auwal; Babati, Abu-Hanifa (FUDMA JOURNAL OF SCIENCES, 2022)
This study examined the influence of climate indices on vegetation dynamics in Kamuku national park, Nigeria. MODIS NDVI dataset was obtained from 2000 – 2021, while temperature and rainfall data were obtained from NiMet Kaduna international airport from 1980 - 2015. Downscale climate indices from Six-generation (Coupled Model Intercomparison Project Phase 6 (CMIP 6)) global climate model was obtained from Copernicus from 1850 - 2099. Coefficient of variability, Mann Kendall and correlation were used to examine the variability, trend and relationship. Subsequently, multiple linear regression was used to assess the influence of climate indices on vegetation dynamics. The result revealed that rainfall indices have moderate variability and temperature indices show a low variability, while the normalized vegetation index revealed a low variability of vegetation vigour in the study area.  In addition, there is a weak positive relationship between the rainfall indices and vegetation and a negative relationship between temperature indices and the vegetation vigour. The climate indices were able to explain 47 % (R2 = 0.47) variance of the vegetation vigour in Kamuku national park. While the remaining 53% might be a result of other factors such as human activities and other environmental factors. In conclusion, the vegetation vigour regulates the distribution of the climate extreme indices and might likely be more influenced by the human activities
Keywords: climate indices, vegetation, protected area, Kamuku national park, regression